Preliminary study on detection of basal stem rot (BSR) disease at oil palm tree using electrical resistance - Esa, Nurnadiah; Wayayok, Aimrun; Mohd Soom, Mohd Amin; A. S., Idris (Elsevier, 2014)
BSR disease attack oil palm in Malaysia caused by Ganoderma boninense which resulted in the destruction of basal tissues of the plant. The study was aimed to detect healthy and an infected tree by using electrical resistance (ER). LandMapperERM-2 was used to detect the diseases by collecting ER data at eight positions surrounding the trunk at three different levels of height for each tree. Tree that has been infected gives low ER readings between 0 Ω to 24.9Ω while for the healthy tree have 25 Ω to 150Ω. Hence, ER approach can be utilized in detecting unhealthy oil palm tree.